Diabetes Mellitus and Metformin: Fatal Vitamin B12 Deficiency Associated with Anemia and Sepsis in a Young Adult - Anuvarsha Katroth, Anusha Narayanam, Sheetal Chauhan, Ajit Singh (Journal of Applied Pharmaceutical Science, 2018)
Metformin is recommended as the first-line therapy to treat type 2 diabetes mellitus with better efficacy. We present a young adult with severe fatigue and dyspnea along with difficulty during the walk and tingling sensation in both the lower limbs. He had T2DM for 9 years and continuing metformin 1 g daily for five years. He presented to the hospital with untreated wounds over lower limbs. His haematological reports showed the megaloblastic anemia and transfused with several pints of packed red blood cells (PRBCs). The patient developed sepsis during hospitalization and started on antibiotics. After several PRBC transfusions and aggressive treatment also patient did not improve and succumbed on 5th day of hospitalization.
Keywords: Megaloblastic anemia, Met¬formin-induced neuropathy, Diabetic foot, Diabetic ulcers.